Wissenskulturen im Dialog Experimentalräume zwischen Wissenschaft und Kunst - Ingrisch, Doris 1957-; Mangelsdorf, Marion; Dressel, Gert 1964- (Edition Kulturwissenschaft, 2017)
Encounters between different cultures of knowledge can be unsettling for both parties. Everything that in one academic or artistic discipline is considered secure knowledge loses its self-evidence in the face of both inter-, trans-, and post-disciplinary